Using the Angoff method to set a standard on mock exams for the Korean Nursing Licensing Examination - Yim, Mi Kyoung; Shin, Sujin (Journal of educational evaluation for health professions, 2020)
Purpose: This study explored the possibility of using the Angoff method, in which panel experts determine the cut score of an exam, for the Korean Nursing Licensing Examination (KNLE). Two mock exams for the KNLE were analyzed. The Angoff standard setting procedure was conducted and the results were analyzed. We also aimed to examine the procedural validity of applying the Angoff method in this context.Methods: For both mock exams, we set a pass-fail cut score using the Angoff method. The standard setting panel consisted of 16 nursing professors. After the Angoff procedure, the procedural validity of establishing the standard was evaluated by investigating the responses of the standard setters.Results: The descriptions of the minimally competent person for the KNLE were presented at the levels of general and subject performance. The cut scores of first and second mock exams were 74.4 and 76.8, respectively. These were higher than the traditional cut score (60% of the total score of the KNLE). The panel survey showed very positive responses, with scores higher than 4 out of 5 points on a Likert scale.Conclusion: The scores calculated for both mock tests were similar, and were much higher than the existing cut scores. In the second simulation, the standard deviation of the Angoff rating was lower than in the first simulation. According to the survey results, procedural validity was acceptable, as shown by a high level of confidence. The results show that determining cut scores by an expert panel is an applicable method.